Forgiveness and Altruism as predictors of Psychological Well- Being - Rani, Sarita; Kumar, Ramesh (International Journal of Psychosocial Rehabilitation, 2020)
The present study was aimed to explore forgiveness and altruism as the predictor of psychological well- being. The participants comprised of 100 university adolescents. In order to collect data, the Heartland’s Scale of Forgiveness, Self-Report Altruism Scale and Ryff’s Psychological Well-being scale were used. Data were analyzed through Pearson correlation, t-test and stepwise linear regression. Results of the study indicated that forgiveness and altruism showed a significant positive relationship with psychological well-being. Also, both altruism (ß=.771, p=000) and forgiveness (ß=.503, p=000) predict psychological well-being in a significant manner. The study also revealed that adolescent’s females differ significantly on forgiveness. Adolescent’s females showed high forgiveness level than male adolescents. Thus, positive psychological resources like forgiveness and altruism are indeed essential for enhancing one’s psychological well-being. The implications of the findings are also discussed in the light of empirical pieces of evidence.